2021
DOI: 10.1080/02688697.2021.1940853
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for differentiating grade II meningiomas from grade I: a systematic review

Abstract: IntroductionThere are a number of prognostic markers (methylation, CDKN2A/B) described to be useful for the stratification of meningiomas. However, there are currently no clinically validated biomarkers for the preoperative prediction of meningioma grade, which is determined by the histological analysis of tissue obtained from surgery.Accurate preoperative biomarkers would inform the pre-surgical assessment of these tumours, their grade and prognosis and refine the decision-making process for treatment. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…Validating clinically useful prognostic markers remains a major challenge in neuro-oncology. The availability of accurate preoperative biomarkers in MGM patients would improve the pre-surgical assessment of these tumors, their grade and clinical prognosis, and help direct treatment decisions [43]. Advances in the identification of biomarkers in liquid biopsies using samples of cerebrospinal fluid and blood should enable the development of less invasive diagnostic and prognostic methods that will also allow the monitoring of treatment efficacy during disease [83].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Validating clinically useful prognostic markers remains a major challenge in neuro-oncology. The availability of accurate preoperative biomarkers in MGM patients would improve the pre-surgical assessment of these tumors, their grade and clinical prognosis, and help direct treatment decisions [43]. Advances in the identification of biomarkers in liquid biopsies using samples of cerebrospinal fluid and blood should enable the development of less invasive diagnostic and prognostic methods that will also allow the monitoring of treatment efficacy during disease [83].…”
Section: Discussionmentioning
confidence: 99%
“…Many radiological, plasmatic, histological, and molecular prognostic markers have been put forward to help to stratify MGMs. However, to date there are no clinically validated biomarkers to help inform determination of tumor grade and clinical prognosis [20,43]. Investigation of gene expression features of progressing, recurrent, or grade III MGM tumors revealed that notably aggressive tumor subsets share a substantial group of differentially expressed genes, in addition to identifying genes separating non-recurring from recurrent and malignant grade I or grade II tumors.…”
Section: Current and Candidate Biomarkers In Mgmmentioning
confidence: 99%
See 2 more Smart Citations
“…Many radiological, plasmatic, histological, and molecular prognostic markers have been put forward to help to stratify MGMs. However, to date there are no clinically validated biomarkers to help inform the determination of tumor grade and clinical prognosis [ 21 , 44 ]. Investigation of gene expression features of progressing, recurrent, or grade III MGM tumors revealed that notably aggressive tumor subsets share a substantial group of differentially expressed genes, in addition to identifying genes separating non-recurring from recurrent and malignant grade I or grade II tumors.…”
Section: Current and Candidate Biomarkers In Mgmmentioning
confidence: 99%